Cancer Mortality Trends and Predictions for 2024 in Italy - Silvia Mignozzi; Claudia Santucci; Eva Negri; Carlo La Vecchia (Epidemiology, Biostatistics and Public Health)
The prediction of numbers and trends for cancer mortality is useful for evaluating disease burden worldwide and reflects the impact of incidence, screening and advancement in early diagnosis and treatments for major cancer sites. Following our recent publication on the estimation of the number of cancer deaths and the corresponding mortality rates for all cancers and selected major cancer sites for the year 2024 in the European Union and the UK [1], here we provide corresponding figures for Italy.